2014
DOI: 10.1371/journal.pone.0101477
|View full text |Cite
|
Sign up to set email alerts
|

Is Peripheral Immunity Regulated by Blood-Brain Barrier Permeability Changes?

Abstract: S100B is a reporter of blood-brain barrier (BBB) integrity which appears in blood when the BBB is breached. Circulating S100B derives from either extracranial sources or release into circulation by normal fluctuations in BBB integrity or pathologic BBB disruption (BBBD). Elevated S100B matches the clinical presence of indices of BBBD (gadolinium enhancement or albumin coefficient). After repeated sub-concussive episodes, serum S100B triggers an antigen-driven production of anti-S100B autoantibodies. We tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 76 publications
2
56
0
Order By: Relevance
“…Authors concluded that the stress of combat training increases inflammatory mediators and propose alterations in the BBB permeability as one of the mechanisms for cognitive dysfunction under stress (Li et al, 2014). The role of peripheral immunity in regulating BBB permeability has also been reported (Bargerstock et al, 2014). The findings of our study are in accordance with previous studies in animal models, which demonstrated that chronic trauma during early development produced increased levels of S100B (Sharma and Dey, 1981; Diehl et al, 2007; Margis et al, 2004; Scaccianoce et al, 2004; Friedman et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Authors concluded that the stress of combat training increases inflammatory mediators and propose alterations in the BBB permeability as one of the mechanisms for cognitive dysfunction under stress (Li et al, 2014). The role of peripheral immunity in regulating BBB permeability has also been reported (Bargerstock et al, 2014). The findings of our study are in accordance with previous studies in animal models, which demonstrated that chronic trauma during early development produced increased levels of S100B (Sharma and Dey, 1981; Diehl et al, 2007; Margis et al, 2004; Scaccianoce et al, 2004; Friedman et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This breakdown of the blood brain barrier can lead to infiltration of pathogenic systemic inflammatory mediators, immune cells or other toxic substances into the brain that may promote epileptogenesis (Fabene et al, 2008; Ivens et al, 2007). In fact, astrocytic proteins may be involved in triggering peripheral immune responses in the context of brain injury and blood brain barrier breakdown (Bargerstock et al 2014; Marchi et al 2013; Zhang et al 2014). In contrast to epilepsy related to acquired brain injuries, much less is known about a potential role of systemic inflammation in genetic epilepsies such as TSC.…”
Section: Discussionmentioning
confidence: 99%
“…Available tools include microangiography (Cavaglia et al, 2001), 2-photon microscopy (Iliff et al, 2013b), magnetic resonance imaging (MRI) and serum markers (Bargerstock et al, 2014; Janigro et al, 2013b; Kanner et al, 2003; Marchi et al, 2012b). Fluorescent Dextrans or Albumin has been used to visualize regional cerebrovascular morphology, damage and the pattern of interstitial protein accumulation (Boussadia et al, 2014; Cavaglia et al, 2001; Fan et al, 2008; Hallene et al, 2006).…”
Section: Visualization Of the Blood–brain Barrier And Parenchymal mentioning
confidence: 99%